2020
DOI: 10.1684/mrh.2020.0470
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency with high calcium-to-magnesium ratio promotes a metastatic phenotype in the CT26 colon cancer cell line

Abstract: Magnesium (Mg) plays important roles in maintaining genomic stability and cellular redox. Mg also serves as nature's physiological calcium (Ca) channel antagonist, controlling intracellular Ca entry. Because Ca is the most important second messenger, its intracellular concentration is tightly regulated. Excess intracellular Ca can activate aberrant signaling pathways leading to the acquisition of pathological characteristics and cell injury. Several epidemiological studies have linked Mg deficiency (MgD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
(72 reference statements)
0
4
0
Order By: Relevance
“…Previous studies aimed at addressing mechanistic insights on the protective effect of Mg on vascular cells gave relevance to the properties of Mg as a calcium antagonist, 1 so that calcium action is susceptible of being modified by the Mg supplement. A rise in the intracellular calcium can activate transduction pathways leading to an increase in oxidative stress, the activation of the NF‐κB signalling and the production of pro‐inflammatory cytokines 49,50 . Thus, as a physiological inhibitor of calcium channels, Mg might prevent calcium flux and therefore the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies aimed at addressing mechanistic insights on the protective effect of Mg on vascular cells gave relevance to the properties of Mg as a calcium antagonist, 1 so that calcium action is susceptible of being modified by the Mg supplement. A rise in the intracellular calcium can activate transduction pathways leading to an increase in oxidative stress, the activation of the NF‐κB signalling and the production of pro‐inflammatory cytokines 49,50 . Thus, as a physiological inhibitor of calcium channels, Mg might prevent calcium flux and therefore the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a Ca/Mg ratio between 1.70 and 2.6 may be required for high intakes of Ca and Mg to be protective (62). Interestingly, a recent in vitro study using the CT26 colon cancer cell line showed that with Ca/Mg ratios >1, Mg deficiency resulted in oxidative stress and NF-κB p65 activation, while this was not observed with a Ca/Mg ratio of 1 (50). Though a possible modifying effect of the Ca/Mg intake ratio cannot be totally discarded in our in vivo model, it would not likely be much relevant as it is usually important when magnesium or calcium are provided in deficient or barely adequate amounts, which is not the case.…”
Section: Nf-κb Plays a Major Role In Inducing The Expression Of Inflammatory Cytokines Inmentioning
confidence: 99%
“…These outcomes were more pronounced in the metastatic group, suggesting a potential association between Mg 2+ release and the inhibition of distant colorectal cancer metastasis. [ 33 ] Subsequently, we quantified the number of infiltrating immune cells at primary and metastatic sites. Notably, effector T (CD45 + , CD3 + , and CD8 + ) and cytotoxic T cells (CD3 + , CD8 + , and IFN‐γ + ) were markedly elevated in the MHM and MHMO groups at the primary location, with infiltration further accentuated following piezoelectric stimulation (Figure 5d–g ).…”
Section: Resultsmentioning
confidence: 99%
“…The calcium/magnesium intake ratio and their balance regulated by parathyroid hormone and TRPM7 have been implicated in the development of colorectal carcinoma [141,142]. Furthermore, magnesium deficiency with physiological Ca 2+ concentrations (i.e., increased Ca 2+ /Mg 2+ ratio) was associated with increased TRPM7 expression, oxidative stress, induced calpain activity, increased cell migration and a more aggressive, metastatic phenotype of colon cancer cells [143] (Table 6).…”
Section: Colorectal Carcinomamentioning
confidence: 99%